Proceedings of the International Conference on Web Search and Web Data Mining - WSDM '08 2008
DOI: 10.1145/1341531.1341554
|View full text |Cite
|
Sign up to set email alerts
|

Understanding temporal aspects in document classification

Abstract: Due to the increasing amount of information present on the Web, Automatic Document Classification (ADC) has become an important research topic. ADC usually follows a standard supervised learning strategy, where we first build a model using pre-classified documents and then use it to classify new unseen documents. One major challenge for ADC in many scenarios is that the characteristics of the documents and the classes to which they belong may change over time. However, most of the current techniques for ADC ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
(21 reference statements)
1
32
0
1
Order By: Relevance
“…Salles et al [8] have discussed the impact that temporal effects may have on Automatic Document Classification and how to minimize such impact. Previous researches have shown that temporal effects, such as the variation of the strength of term-class relationship over time, have a significant impact on Automatic Document Classification [9]. To deal with the effect of term-class relationship over time Salles et al [8] have introduced a temporal weighting function and have extended the classification algorithms to incorporate the temporal weighting function.…”
Section: Related Workmentioning
confidence: 99%
“…Salles et al [8] have discussed the impact that temporal effects may have on Automatic Document Classification and how to minimize such impact. Previous researches have shown that temporal effects, such as the variation of the strength of term-class relationship over time, have a significant impact on Automatic Document Classification [9]. To deal with the effect of term-class relationship over time Salles et al [8] have introduced a temporal weighting function and have extended the classification algorithms to incorporate the temporal weighting function.…”
Section: Related Workmentioning
confidence: 99%
“…Mourao et al present an empirical analysis of temporal data on news classification [11]. The impact of empirical methods in information extraction is described by Cardie in [3].…”
Section: Related Workmentioning
confidence: 99%
“…A work that met these requirements is [Mourão et al 2008] where the authors characterized textual documents evolving through the time. They presented evidences of this evolution as metrics and experiments that confirmed it.…”
Section: Related Workmentioning
confidence: 99%
“…They presented evidences of this evolution as metrics and experiments that confirmed it. Another work in this same subject was [Salles 2011] that redid the analysis presented in [Mourão et al 2008] for an additional dataset. He also applied factorial projects techniques [Jain 1991] to identify the impact of variations in the classification algorithms.…”
Section: Related Workmentioning
confidence: 99%